2014
DOI: 10.1111/dom.12290
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced reduction of postprandial glucagon by lixisenatide: a meta‐analysis of randomized clinical trials

Abstract: Lixisenatide significantly reduced 2-h PPG and glucose excursion together with a marked reduction in postprandial glucagon and insulin; thus, lixisenatide appears to have biological effects on blood glucose that are independent of increased insulin secretion. These effects may be, in part, attributed to reduced glucagon secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 42 publications
5
33
0
1
Order By: Relevance
“…Baseline HbA1c was the characteristic most closely associated with a glycemic response to saxagliptin. This is consistent with findings that higher baseline HbA1c is associated with a greater reduction in HbA1c with DPP-4 inhibitors [21,24] and other oral antidiabetes medications [25]. HOMA-2%β values can be a functional result (insulin secretion stimulated pharmacologically) rather than a biological improvement in β-cell functionality.…”
Section: Discussionsupporting
confidence: 89%
“…Baseline HbA1c was the characteristic most closely associated with a glycemic response to saxagliptin. This is consistent with findings that higher baseline HbA1c is associated with a greater reduction in HbA1c with DPP-4 inhibitors [21,24] and other oral antidiabetes medications [25]. HOMA-2%β values can be a functional result (insulin secretion stimulated pharmacologically) rather than a biological improvement in β-cell functionality.…”
Section: Discussionsupporting
confidence: 89%
“…An important evidence for this was the demonstration that subjects with type 2 diabetes had higher baseline glucagon levels than non-diabetic subjects and these levels were not suppressed by a carbohydrate meal, as was the case in the non-diabetics [47]. The hyperglucagonemia in type 2 diabetes which is less suppressible by raising glucose has been confirmed in many studies [48] and is clearly evident by the correlation in improvement in glycemia and reduction in glucagon by dipeptidyl peptidase-4 (DPP-4) inhibition [49] and GLP-1 receptor agonism [50]. We have also in our long-term population study in Malmö evaluated the contribution of perturbations in glucagon secretion for changes in glucose tolerance.…”
Section: Glucagon Is An Important Player In Diabetesmentioning
confidence: 99%
“…This has been enforced by the successful improvement of hyperglycemia by DPP-4 inhibition and GLP-1 receptor agonism in association with reduction in glucagon [49,50]. The first demonstration that GLP-1 reduces glucagon diabetes was presented by Gutniak et al, who showed that GLP-1 infusion in subjects with type 2 diabetes reduced glucagon levels after meal ingestion ( Fig.…”
Section: Glucagon Is a Target For Treatment Of Diabetesmentioning
confidence: 99%
“…Lixisenatide significantly decreases HbA 1c and postprandial glucose when used as monotherapy or add-on therapy [210][211][212][213][214][215][250][251][252][253][254][255][256][257] . In a meta-analysis of RCTs, compared with placebo, lixisenatide treatment produced reductions in 2 h postprandial glucose from baseline (LSMD −4.9 mmol/l, P <0.001), glucose excursion (LSMD −4.5 mmol/l, P <0.001) and postprandial glucagon (LSMD −19.0 ng/l, P <0.001) 256 .…”
Section: Pharmacodynamicsmentioning
confidence: 99%